Computational Analysis of the Molecular Graph and the Line Graph of Glass by Studying Their M-Polynomial and Topological Indices - Tousi, Jaber Ramezani; Ghods, Masoud (Discontinuity, Nonlinearity, and Complexity, 2026)
Glass is an amorphous non-crystalline solid and often transparent that has wide applications in architecture, tableware, optics, and optoelectronics. ewline In this article, first, the mathematical relationship between M-polynomial and topological indices such as Revan indices, Gourava indices, and Y-index are obtained. Then M-polynomial is computed for the molecular graph and the line graph of Glass. Finally, using M-polynomial, Revan indices, Gourava indices, and Y-index are calculated.